2013
DOI: 10.3945/ajcn.112.045781
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal omega-3 (n-3) LCPUFA supplementation during pregnancy on early childhood cognitive and visual development: a systematic review and meta-analysis of randomized controlled trials

Abstract: The evidence does not conclusively support or refute that omega-3 LCPUFA supplementation in pregnancy improves cognitive or visual development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(136 citation statements)
references
References 54 publications
(153 reference statements)
5
126
2
3
Order By: Relevance
“…[23][24][25][26][27][28] These studies have been extensively reviewed and results are currently inconclusive. [29][30][31][32] Contrasting results from n-3 DHA trials may be due differences in timing or exposure as well as type and dose of n-3 DHA supplementation. Another possible explanation is that total n-3 DHA exposure (total intake from food and supplemental sources) has not been accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] These studies have been extensively reviewed and results are currently inconclusive. [29][30][31][32] Contrasting results from n-3 DHA trials may be due differences in timing or exposure as well as type and dose of n-3 DHA supplementation. Another possible explanation is that total n-3 DHA exposure (total intake from food and supplemental sources) has not been accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent meta-analyses and systematic reviews have concluded to no clear benefit on child's psychomotor development of supplementing both term and preterm infants with formulas enriched in LC-PUFA (Schulzke et al, 2011;Simmer et al, 2011). Trials supplementing pregnant or lactating women with fish-oil rich in LC-PUFA have not resulted in more evidence regarding similar outcomes in children (Delgado-Noguera et al, 2010;Gould et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of supplementation on visual acuity in term infants has also been shown (Birch et al 2005), but not consistently. In addition, the effects of oral supplementation of omega-3 fatty acids during pregnancy on early childhood development, especially visual, were inconclusive (Gould et al 2013). In a meta-analysis of 12 studies (1949 infants up to 12 months of age), omega-3 supplementation of infant formulas appeared to have possible effects on visual acuity as measured by evoked potential for infants 2 months of age and by behavioral methods at 12 months (Qawasmi et al 2013).…”
Section: Neurological Developmentmentioning
confidence: 99%